Causes of in-hospital mortality after hip fractures in the elderly. Issue 2 (March 2020) - Groff, Hannah; Kheir, Michael M; George, Jaiben; Azboy, Ibrahim; Higuera, Carlos A; Parvizi, Javad
Objectives: Although there are numerous studies reporting early mortality after hip fracture, the incidence and aetiology of in-hospital mortality following hip fractures is largely unknown. This study aimed to determine the causes and the incidence of in-hospital mortality in patients with a hip fracture who received surgical treatment. Methods: This was a multi-institutional retrospective study identifying 2464 consecutive patients >65 years of age who were treated for a hip fracture from 2000 to 2016 at 2 institutions. Revision surgeries were excluded. An electronic query followed by manual chart review was performed to collect patient demographics, Charlson comorbidity index (CCI), type of anaesthesia, and cause of death. Results: The overall in-hospital mortality rate for patients undergoing surgical intervention for an acute hip fracture was 3.0% (75/2464). The most common causes of death in descending order were: respiratory failure ( n = 26), cardiac failure ( n = 13), multiorgan failure ( n = 6), septic shock ( n = 6), pulmonary embolism ( n = 5), end stage renal disease ( n = 5) and others ( n = 14). In-hopsital mortality was associated with older age ( p = 0.001) and higher CCI scores ( p = 0.001). There was no association with gender ( p = 0.165), type of anaesthesia ( p = 0.497), extracapsular versus intracapsular fracture ( p = 0.627), pathologic versus non-pathologic fracture (0.799), or body mass index ( p = 0.781). Conclusion: This study demonstrated that hip fracture patients are at relatively high risk of in-hospital mortality following surgical intervention with a high proportion of patients succumbing to respiratory failure. The findings compel us to investigate strategies that can minimize mortality related to respiratory failure in this patient population such as minimising opioid use, early mobilisation, and implementing greater respiratory monitoring.